Bladder Dysfunction in Diabetes Mellitus - Golbidi, Saeid; Laher, Ismail (Frontiers in Pharmacology, 2010)
Diabetic cystopathy is a well-recognized complication of diabetes mellitus that usually develops in middle-aged or elderly patients with long-standing and poorly controlled hyperglycemic disease and can have a broad-spectrum clinical presentation. Patients may be asymptomatic, or have a wide variety of voiding complaints from overactive bladder and urge incontinence to decreased bladder sensation and overflow incontinence. This review focuses on the pathophysiological mechanisms responsible for the urologic complications of diabetes and emphasizes recent developments in our understanding of this condition. We also elaborate on therapeutic modalities such as the behavioral, pharmacological and surgical approaches to management of diabetic cystopathy.